Can developing countries achieve adequate improvements in child health outcomes without engaging the private sector? - Flavia Bustreo; April Harding; Henrik Axelsson (Bulletin of the World Health Organization)
The private sector exerts a significant and critical influence on child health outcomes in developing countries, including the health of poor children. This article reviews the available evidence on private sector utilization and quality of care. It provides a framework for analysing the private sector's influence on child health outcomes. This influence goes beyond service provision by private providers and nongovernmental organizations (NGOs). Pharmacies, drug sellers, private suppliers, and food producers also have an impact on the health of children. Many governments are experimenting with strategies to engage the private sector to improve child health. The article analyses some of the most promising strategies, and suggests that a number of constraints make it hard for policy-makers to emulate these approaches. Few experiences are clearly described, monitored, and evaluated. The article suggests that improving the impact of child health programmes in developing countries requires a more systematic analysis of how to engage the private sector most effectively. The starting point should include the evaluation of the presence and potential of the private sector, including actors such as professional associations, producer organizations, community groups, and patients' organizations.